Steps in entering a premise / Shahmi Faiz Shahar and Siti Fairuz Ibrahim - Shahar, Shahmi Faiz; Ibrahim, Siti Fairuz (Faculty of Art and Design, 2021)
‘Steps in Entering A Premise E-Learning’ is about how and what are the safety steps that your children should take when entering any premises under current circumstances. It is important for everyone to take precaution and be safe against this new coronavirus disease. Interactive learning package with animated graphics, sound, voice, and other interactive elements. Nowadays, many interactive digitals have been created on apps either on personal computers or mobile devices. All interactive products have made huge impacts in the creative industry and helped to increase Malaysian’s economy. The creative industry is blossoming rapidly due to easy availability especially on mobile phones and mobile tabs. Interactive learning makers compete in developing interactive learning concepts and characters to be the best in the market. There are efforts in making education more fun and innovative using the concept of interactive learning application. Moreover, this product is about exploring the opportunities in making learning through 2D animation interactive learning orientation.